Region‐specific impairments in striatal synaptic transmission and impaired instrumental learning in a mouse model of Angelman syndrome. (13th December 2013) - Hayrapetyan, Volodya; Castro, Stephen; Sukharnikova, Tatyana; Yu, Chunxiu; Cao, Xinyu; Jiang, Yong‐Hui; Yin, Henry H.
Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder characterized by mental retardation and impaired speech. Because patients with this disorder often exhibit motor tremor and stereotypical behaviors, which are associated with basal ganglia pathology, we hypothesized that AS is accompanied by abnormal functioning of the striatum, the input nucleus of the basal ganglia. Using mutant mice with maternal deficiency of AS E6‐AP ubiquitin protein ligase Ube3a ( Ube3a m−/p+ ), we assessed the effects of Ube3a deficiency on instrumental conditioning, a striatum‐dependent task. We used whole‐cell patch‐clamp recording to measure glutamatergic transmission in the dorsomedial striatum (DMS) and dorsolateral striatum (DLS). Ube3a m−/p+ mice were severely impaired in initial acquisition of lever pressing. Whereas the lever pressing of wild‐type controls was reduced by outcome devaluation and instrumental contingency reversal, the performance of Ube3a m−/p+ mice were more habitual, impervious to changes in outcome value and action–outcome contingency. In the DMS, but not the DLS, Ube3a m−/p+ mice showed reduced amplitude and frequency of miniature excitatory postsynaptic currents. These results show for the first time a selective deficit in instrumental conditioning in the Ube3a deficient mouse model, and suggest a specific impairment in glutmatergic transmission in the associative corticostriatal circuit in AS. Abstract : Using mutant mice with maternal deficiency of AS E6‐AP ubiquitin protein ligase Ube3a ( Ube3a m−/p+ ), we assessed the effects of Ube3a deficiency on instrumental conditioning and striatal glutamatergic synaptic transmission. We show for the first time a selective deficit in instrumental conditioning in the Ube3a deficient mouse model, and suggest a specific impairment in glutmatergic transmission in the associative corticostriatal circuit in AS.